Point Measurement Techniques and Radar Remote Sensing Technique Using for Soil Moisture Estimation: A Literature Review - Chamoli, Vivek; Prakash, Rishi; Vidyarthi, Anurag (Journal of Graphic Era University, 2021)
In spite of the fact that previous researchers have utilized different systems of moisture content assurance of soils. In this specific situation, analysts have built up a few systems for estimating the soil moisture eg., thermo gravimetric, neutron dissipating, soil resistivity, dielectric methods and Radar Remote Sensing method using SAR (Synthetic-aperture radar) images. Be that as it may, these methods are very mind boggling, costly (because of very intricate hardware and gear) and henceforth past the span of many. This audit accentuates that why it winds up basic to assess different techniques utilized by the analysts for assurance of the soil moisture. Likewise, a necessity for finding new soil moisture estimation methods or altering the current strategies has been surveyed.